Eating behaviour, quality of life and cardiovascular risk in obese and overweight children and adolescents: a cross-sectional study - Fernanda Gabriela Colombo Drumond Santos; Mariana Godoy-Leite; Eduardo Augusto Resende Penido; Kennad Alves Ribeiro; Maria da Gloria Rodrigues-Machado; Bruno Almeida Rezende (BMC, 2023)
Abstract Background Childhood obesity is a major cardiovascular risk factor because it predisposes individuals to comorbidities that are implicated in an increased risk of cardiovascular events. Its origin may be related to poor eating habits, such as the intake of foods of low nutritional value or inadequate eating behaviours related to emotional factors. This work aims to evaluate the relationship between the total body mass of children and adolescents and its association with eating habits, quality of life (QoL), and possible changes in early markers of cardiovascular risk. Methods This was a cross-sectional observational study that evaluated anthropometric and cardiovascular parameters, QoL, and eating behaviour in 181 children and adolescents aged between 5 and 13 years. Participants were stratified according to BMI/age into three groups (Adequate Weight, Overweight, and Obesity). Anthropometry included weight, height, waist and hip circumferences, waist-hip ratio, and waist-height ratio. QoL was assessed using the Peds-QL 4.0 questionnaire, and eating behaviour was assessed using the Children's Eating Behaviour Questionnaire (CEBQ). Cardiovascular parameters were assessed using the Mobil-O-Graph® device, which measures the pulse wave velocity (PWV) and augmentation index (AIx@75) to estimate arterial stiffness (AS), which is considered an early marker of cardiovascular disease. Results In addition to the increase in anthropometric measurements (p < 0.001), the Obesity group exhibited behaviour related to food intake (p < 0.05). When analysing QoL, a worsening in the social domain was also observed in the Obesity group (p < 0.05). However, PWV and AIx@75 did not differ between groups. Conclusions Eating behaviour is related to the development of childhood obesity. However, early markers of cardiovascular risk related to AS did not change as a function of total body mass in the children evaluated.